Reassessing Islamic Banking Supervision in Indonesia: A Contemporary Islamic and Socio-Legal Perspective on OJK’s Integrated Model - Hasan; Teng Berlianty; Merry Tjoanda; Juanrico Alfaromona Sumarezs Titahelu; Mualimin Mochammad Sahid (Faculty of Sharia, IAIN Metro, 2025)
This article reassesses the effectiveness of the Financial Services Authority’s (OJK) integrated and independent supervisory model in overseeing Islamic banking in Indonesia. At the same time, the model has improved coordination and regulatory efficiency across the financial sector and aligned with Islamic legal principles. Using a normative legal approach supported by socio-legal analysis, the study evaluates how far OJK’s supervisory framework reflects key Islamic values. It draws on statutory regulations, fatwas issued by DSN-MUI, and international standards from institutions like the Basel Committee and the IFSB while incorporating comparative insights from countries like the UK and Germany. The study finds that although OJK’s model is risk-based and structurally sound, it tends to focus more on technical compliance than Sharia's substantive objectives. Key challenges include the limited integration of DSN-MUI fatwas into binding regulatory processes, weak collaboration between OJK and Sharia supervisory boards, and the lack of performance indicators that reflect Sharia values in bank evaluations. Furthermore, global regulatory benchmarks have not been fully adapted to the distinct characteristics of Islamic financial contracts and Sharia-based governance. This article contributes academically by offering a more holistic perspective on financial supervision that bridges positive law and Islamic normative ethics. It recommends strengthening institutional synergy, embedding Sharia objectives into regulatory metrics, and adopting a more responsive, community-grounded supervisory approach. Through these efforts, Indonesia’s Islamic banking sector can become more sustainable, credible, and aligned with national interests and Islamic legal ideals.